2013
DOI: 10.1002/art.37926
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Bone Mineral Density to Progression of Knee Osteoarthritis

Abstract: Objective We sought to evaluate the longitudinal relationship of bone mineral density (BMD) and its change to knee osteoarthritis (OA) progression measured by cartilage outcomes. Methods We used observational cohort data from the Vitamin D for Knee Osteoarthritis trial. We obtained bilateral femoral neck BMDs as well as knee MRIs in each subject at baseline and subsequently at 12 and 24 months. We measured change in total cartilage volume, tibial and femoral cartilage thickness by manual cartilage segmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 30 publications
1
30
1
Order By: Relevance
“…These results are in agreement with a previous study, reporting a decrease in periarticular subchondral BMD in mild OA patients [23]. In addition, Lee et al [24] reported that BMD loss was associated with progressive cartilage loss in knees with OA. Overall, it is inferred that OVX-induced osteoporosis and ACLT with MM-induced cartilage damage led to BMD decrease.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with a previous study, reporting a decrease in periarticular subchondral BMD in mild OA patients [23]. In addition, Lee et al [24] reported that BMD loss was associated with progressive cartilage loss in knees with OA. Overall, it is inferred that OVX-induced osteoporosis and ACLT with MM-induced cartilage damage led to BMD decrease.…”
Section: Discussionsupporting
confidence: 93%
“…In a clinical trial of 42 surgical patients with pre-arthritic cartilage lesions, smoking was associated with worse cartilage outcomes due to inhibition of important mediators of cartilage metabolism, IGF-1 and bFGF 41 . Smokers are also at risk for reduced bone density 42 and a 2013 study of radiographcially confirmed knee OA patients (K-L grade ≥2) found that longitudinal bone mineral density loss was associated with progressive knee cartilage loss 43 . Susceptibility to knee OA may be genetic 44 and in one study an association was found between smoking and knee cartilage loss among those with a family history of knee OA while controls (smoking with no family history of knee OA) had no such association 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Although an inverse relationship between OA and osteoporosis has been suggested (reviewed in [11]), different reports indicate that osteopenia and osteoporosis occur in a significant proportion of patients with severe knee or hip OA [12] and longitudinal bone mineral density loss, at a site remote from the knee, is associated with progressive loss of cartilage in OA knees [13]. Several studies have also shown that changes in bone can be detected early in the development of OA with osteoporosis subjacent to the subchondral sclerosis area [14] and within the tibiae of patients with knee OA [15].…”
Section: Introductionmentioning
confidence: 97%